In search of basic units of spoken language a corpus-driven approach - Izre'el, Shlomo; Mello, Heliana; Panunzi, Alessandro; Raso, Tommaso (Studies in corpus linguistics (SCL),, 2020)
"What is the best way to analyze spontaneous spoken language? In their search for the basic units of spoken language the authors of this volume opt for a corpus-driven approach. They share a strong conviction that prosodic structure is essential for the study of spoken discourse and each bring their own theoretical and practical experience to the table. In the first part of the book they segment spoken material from a range of different languages (Russian, Hebrew, Central Pomo (an indigenous language from California), French, Japanese, Italian, and Brazilian Portuguese). In the second part of the book each author analyzes the same two spoken English samples, but looking at them from different perspectives, using different methods of analysis as reflected in their respective analyses in Part I. This approach allows for common tendencies of segmentation to emerge, both prosodic and segmental"--